Ethnic Differences in Thrombotic Profiles of Acute Coronary Syndrome Patients and Relationship to Cardiovascular Outcomes: A Comparison of East Asian and White subjects - Suh, Jung-Won; Memtsas, Vassilios; Gue, Ying X; Cho, Hyoung-Won; Lee, Wonjae; Kang, Si-Hyuck; Gorog, Diana A (Thrombosis and haemostasis, 2024)
East Asians (EAs), compared to white Caucasians (W), have a lower risk of ischemic heart disease and a higher risk of bleeding with antithrombotic medications. The underlying mechanisms are incompletely understood. We sought to compare thrombotic profiles of EA and W patients with myocardial infarction (MI) and relate these to cardiovascular outcomes. In a prospective study in the United Kingdom and Korea, blood samples from patients ( = 515) with ST- or non-ST-elevation MI (STEMI and NSTEMI) were assessed using the Global Thrombosis Test, measuring thrombotic occlusion (OT) and endogenous fibrinolysis (lysis time [LT]). Patients were followed for 1 year for major adverse cardiovascular events (MACE) and bleeding. EA patients showed reduced OT (longer OT) compared to W (646 seconds [470-818] vs. 436 seconds [320-580], < 0.001), with similar LT. In STEMI, OT (588 seconds [440-759] vs. 361 seconds [274-462], < 0.001) and LT (1,854 seconds [1,389-2,729] vs. 1,338 seconds [1,104-1,788], < 0.001) were longer in EA than W. In NSTEMI, OT was longer (OT: 734 seconds [541-866] vs. 580 seconds [474-712], < 0.001) and LT shorter (1519 seconds [1,058-2,508] vs. 1,898 seconds [1,614-2,806], = 0.004) in EA than W patients. MACE was more frequent in W than EA (6.3 vs. 1.9%, = 0.014) and bleeding infrequent. While OT was unrelated, LT was a strong independent predictor of MACE event after adjustment for risk factors (hazard ratio: 3.70, 95% confidence interval: 1.43-9.57, = 0.007), predominantly in W patients, and more so in STEMI than NSTEMI patients. EA patients exhibit different global thrombotic profiles to W, associated with a lower rate of cardiovascular events.